2021
DOI: 10.3389/fphar.2021.584940
|View full text |Cite
|
Sign up to set email alerts
|

The Rise and Fall of Chloroquine/Hydroxychloroquine as Compassionate Therapy of COVID-19

Abstract: The emergence and rapid spread of novel coronavirus disease (COVID-19) has posed a serious challenge to global public health in 2020. The speed of this viral spread together with the high mortality rate has caused an unprecedented public health crisis. With no antivirals or vaccines available for the treatment of COVID-19, the medical community is presently exploring repositioning of clinically approved drugs for COVID-19. Chloroquine (CQ) and hydroxychloroquine (HCQ) have emerged as potential candidates for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“… 281 Chloroquine was first reported to be active against SARS-CoV-2 in vitro in early 2020, which promoted clinical trials and authorization. 264 , 274 , 282 , 283 Later, it faded out of the list of antiviral agents against SARS-CoV-2 with disproved inhibiting infection at the cellular level and protection in clinical practice. 284 286 Mpro/3CLpro and PLpro play essential roles in transforming viral polyprotein into an active form in SARS-COV-2 replication.…”
Section: Molecular Characteristics Of Sequence and The Encoded Protei...mentioning
confidence: 99%
“… 281 Chloroquine was first reported to be active against SARS-CoV-2 in vitro in early 2020, which promoted clinical trials and authorization. 264 , 274 , 282 , 283 Later, it faded out of the list of antiviral agents against SARS-CoV-2 with disproved inhibiting infection at the cellular level and protection in clinical practice. 284 286 Mpro/3CLpro and PLpro play essential roles in transforming viral polyprotein into an active form in SARS-COV-2 replication.…”
Section: Molecular Characteristics Of Sequence and The Encoded Protei...mentioning
confidence: 99%
“…The net value of further trials for hydroxychloroquine outweighed the cost of research, and therefore, the highest net value for this drug was found in the OIR strategy. Nevertheless, this further research would be conducted to investigate decremental cost-effectiveness (saving costs due to reduced survival), the ethical implications of which should be considered (see Table 3 3 , 8 , 20 , 22 , 25 , 37 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…50 Nevertheless, there are countries that continue to recommend its prescription 51 , 52 based on early studies that later received heavy criticism. 53 The WHO announced in June 2020 that the hydroxychloroquine arm of the SOLIDARITY trial was stopped, based on findings from the RECOVERY and SOLIDARITY trials. At least 27 trials investigating hydroxychloroquine have been prematurely terminated and 12 withdrawn before enrollment, 3 and some countries have banned the drug in the treatment of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 Nevertheless there are countries which continue to recommend its prescription 53,54 based on early studies that later received heavy criticism. 55 The WHO announced in June 2020 that the Hydroxychloroquine arm of the SOLIDARITY trial was stopped, based on findings from the RECOVERY and SOLIDARITY trials. At least 27 trials investigating Hydroxychloroquine have been prematurely terminated and 12 withdrawn prior to enrolment 3 , and some countries have banned the drug in the treatment of COVID-19 56 .…”
Section: Current Status Reflections and Other Considerationsmentioning
confidence: 99%